THE SPECIFICS OF JUDICIAL CONSIDERATION OF CRIMINAL CASES OF JUVENILE CRIMES - Karamanova Benazir (Scholar Express Journals, 2024)
The article discusses the features of proceedings in cases of juvenile crimes. The opinions of procedural scientists were given about the specificity of proceedings, where minors are the subject of the crime
Keywords: Proceeding; crime; minor; educator